Glycemic States of Patients Presenting with Acute Ischemic Stroke in Tertiary Care Settings (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the glycemic states of patients presenting with acute ischemic stroke.Methods: 50 patients of acute ischemic stroke presenting to Mayo Hospital within 24 hours of symptom onset were taken. Data about any previous diagnosed diabetes was recorded. Blood glucose levels (BSL) at the time of presentation were measured. The patients who were previously known diabetics and those whose presenting BSL was > 200mg/dl were excluded from the glucose tolerance test (GTT). Rest of the patients were subjected to GTT at day 7.Results: Out of 50 patients, 32(64%) were male and 18(36%) were female. Eight(16%) patients were previously diagnosed diabetics and 11(22%) were newly diagnosed as having diabetes. Twelve(24%) patients had impaired glucose tolerance, whereas another 12(24%) had normal glucose levels both at presentation and on GTT. Seven(14%) patients had blood glucose levels in the hyperglycemic range only at presentation whereas GTT at day 7 showed normal values (transient hyperglycemia). Six(12%) patients were of age 40 years or less and in this age group 4(67%) had normal glucose levels, throughout the study. Forty four(88%) patients were of age greater than 40 years and in this age group only eight(18%) had normal glucose levels, throughout the study.Conclusions: Abnormalities of glucose regulation are fairly common among acute stroke patients and mostly these are unrecognized. Blood glucose levels measurement and a formal GTT at one week should be part of work up of every stroke patient for early diagnosis and management of disturbed glucose metabolism.